Experiments in organizational economics - Goerg, Sebastian J., 1980-; Hamman, John R. (Research in experimental economics, 2017)
Research in Experimental Economics (REXE) Volume 19 entitled 'Experiments in Organizational Economics' highlights the importance of replicating previous economic experiments.